Analysis of the 'Blood Fantasy' Phenomenon from the Perspective of Islamic Da'wah Communication - Najmi Yaritsul Firdaus; Akhmad Muhaini; Mohamad Madum; Umi Nur Rofiqoh; Siti Aminah (STAI Publisistik Thawalib Jakarta, 2025)
The rapid development of digital media has transformed societal communication patterns, while simultaneously giving rise to various forms of deviant content on social media that have the potential to erode religious values, undermine public morality, and challenge the role of Islamic da’wah communication in the digital era. The research gap lies in the limited studies that analyze this phenomenon from the perspective of Islamic da’wah communication, as previous research has primarily focused on legal, psychological, or social media responses. This study examines how Islamic da’wah communication can respond to and counter the proliferation of blood fantasy content in digital spaces. The study aims to analyze this phenomenon and formulate relevant da’wah strategies in the digital era. The methodology employed is a qualitative approach with a case study design, using content documentation, non-participatory netnographic observation, and literature review. Data analysis was conducted using qualitative content analysis and critical discourse analysis. The results indicate that the widespread presence of blood fantasy content on social media reflects weak internalization of religious values, low digital and religious literacy, and the dominance of permissive and hedonistic communication patterns in digital spaces. Such content is not only produced as an individual expression but also gains social legitimacy through user interactions. In this context, Islamic da’wah communication has not yet served as an effective counterbalance to the flow of negative information. This study highlights the importance of preventive, educational, and contextual digital da’wah strategies as a moral counter-narrative